Pelatihan Manajemen Chat GPT dalam Membuat Manuskrip Jurnal Nasional Terakreditasi Bagi Mahasisiwi MPI Universitas Nurul Jadid - Eka Diana; Moh. Rofiki; Shofwatul Ummah; Durratul Ma’nuna; Siti Ratnatus Solehah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Students have difficulty designing or writing manuscripts that will be published in accredited national journals. The purpose of this service is to provide solutions with training and mentoring activities for female students who will or are writing accredited scientific journal manuscripts by utilizing Chat GPT management both theoretically and practically. The action learning method, which consists of several stages starting with preparation, implementation, and evaluation, is the method used in this service, which is carried out face-to-face. The results of this service have a very significant impact on female students in making national journal manuscripts, starting from making titles to pamphlets with Chat GPT management. This can be seen from the test results before and after the training